2015
DOI: 10.1159/000442062
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Management of Pauci-Immune Glomerulonephritis and Vasculitis in Western Countries

Abstract: Background: Pauci-immune glomerulonephritis is the most common cause of aggressive glomerulonephritis and occurs as a renal-limited disease or as a component of systemic necrotizing small-vessel vasculitis. It is characterized by paucity of staining for immunoglobulins, by immunofluorescence along with fibrinoid necrosis and crescent formation by light microscopy, while the vast majority of patients have anti-neutrophil cytoplasmic antibodies (ANCA) in their circulation, which also participate in the pathogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…ANCA can be detected in the serum of most MPA patients, most of which are positive for MPO/PANCA, but a few patients can be positive for PR3/CANCA (10,11). The pathogenesis of AAVs involves a complex interplay network of helper T (TH; TH-17) cells, antigen-presenting cells (APCs), and various cytokines like IL-23, IL-1β, TNFα, myeloperoxidase (MPO), and proteinase 3 (PR3), as well as the complement system (12,13). A variety of environmental factors such as infection and drugs are also believed to be related to ANCA production and vasculitis, among which the reported antithyroid drugs mainly include Tabazole, Propylthiazine, and Methimazole (14).…”
Section: Discussionmentioning
confidence: 99%
“…ANCA can be detected in the serum of most MPA patients, most of which are positive for MPO/PANCA, but a few patients can be positive for PR3/CANCA (10,11). The pathogenesis of AAVs involves a complex interplay network of helper T (TH; TH-17) cells, antigen-presenting cells (APCs), and various cytokines like IL-23, IL-1β, TNFα, myeloperoxidase (MPO), and proteinase 3 (PR3), as well as the complement system (12,13). A variety of environmental factors such as infection and drugs are also believed to be related to ANCA production and vasculitis, among which the reported antithyroid drugs mainly include Tabazole, Propylthiazine, and Methimazole (14).…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of pauci-immune renal-limited glomerulonephritis in the USA has been found to be around 3 per million per year with a rate being observed higher in white people [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gold standard treatment for patients with PICGN comprises of corticosteroids (intravenous methylprednisolone followed by oral steroids) and cyclophosphamide. [ 11 ] Studies have shown that with immunosuppressive therapy, 5 year survival can be as high as 75% although it can increase morbidity in these patients. [ 12 13 ] Our study shows that 35% patients with PICGN can be ANCA negative on serology.…”
Section: Discussionmentioning
confidence: 99%